2011
DOI: 10.1016/j.eatbeh.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Food thought suppression: A matched comparison of obese individuals with and without binge eating disorder

Abstract: Preliminary studies of non-clinical samples suggest that purposely attempting to avoid thoughts of food, referred to as food thought suppression, is related to a number of unwanted eating- and weight-related consequences, particularly in obese individuals. Despite possible implications for the treatment of obesity and eating disorders, little research has examined food thought suppression in obese individuals with binge eating disorder (BED). This study compared food thought suppression in 60 obese patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
(51 reference statements)
2
17
0
1
Order By: Relevance
“…Like previous studies, we found that food thought suppression correlated positively with binge-eating frequency (Barnes & Tantleff-Dunn, 2010b; Barnes & White, 2010) and participants diagnosed with BED reported higher levels of food thought suppression compared to participants without BED (Barnes et al, 2011). Changes in binge-eating frequency over treatment, however, were unrelated to the FTSI.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Like previous studies, we found that food thought suppression correlated positively with binge-eating frequency (Barnes & Tantleff-Dunn, 2010b; Barnes & White, 2010) and participants diagnosed with BED reported higher levels of food thought suppression compared to participants without BED (Barnes et al, 2011). Changes in binge-eating frequency over treatment, however, were unrelated to the FTSI.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, food thought suppression may be a relatively consistent coping trait analogous to thought suppression, more broadly (Höping & de Jong-Meyer, 2003; Muris et al, 1996). Similar FTSI scores between the sexes replicated a comparison of treatment-seeking individuals with obesity and BED (Barnes et al, 2013a) but this difference is not documented in studies of community participants (Barnes & Tantleff-Dunn, 2010b; Barnes et al, 2011), perhaps reflecting ceiling effects in treatment-seeking samples.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Although Ward and colleagues posited a link between thought suppression and binge eating over 15 years ago [16], only recently has this hypothesis received empirical attention in nonclinical [17,18] and clinical [19] samples. Food thought suppression may have even greater significance for obese persons with disordered eating such as binge eating disorder (BED).…”
mentioning
confidence: 99%